Soil macrofauna and edaphoclimatic conditions in an altitude gradient of coffee growing regions, Huila, Colombia - Machado Cuellar, Leidy (2021)
Introduction: Soil macrofauna plays a key role in soil processes and therefore regulates the supply of ecosystem services; however, its level of activity depends largely of the edaphoclimatic conditions. Objective: This work evaluated the effect of altitude gradient on soil macrofauna communities and edafoclimatic properties in coffee zones of North Huila. Methods: The study included 12 coffee lots separated in two altitude gradients: low (1 300-1 600 masl) and high (1 600-1 900 masl). Soil macrofauna was collected by means of monoliths (25 x 25 cm with 30 cm depth) and edaphoclimatic conditions were studied. Results: A total of 9 520 individuals m-2 and a specific richness of 14 taxa were registered. The edaphoclimatic conditions with the greatest statistical difference between altitude gradients were the environmental temperature and relative humidity with differences of 4.9 °C and 10.4 %, respectively. Conclusions: The highest abundance of Coleoptera, Hemiptera, Isoptera, Lepidoptera was presented in warmer sites, that is, altitude gradient 1 300-1 600 masl, while Chilopoda and Diplopoda adapted better to colder sites in altitude gradient 1 600-1 900 m.a.s.l.